Handling of the Covid-19 Pandemic in Indonesia: Time to Power Contestation - Hasanah, Umdatul; Rahmat, Ihsan; Halimatusa’diyah, Halimatusa’diyah; Abdullah, Irwan; Musyafak, Najahan (Politicon : Jurnal Ilmu Politik, 2023)
During the handling of the Covid-19 pandemic, the Indonesian government has shown a power contestation. The pandemic turned out to be a stage for actors and policymakers. Some policymakers use the economic approach as power, politics, and regional interests, to the medical power approach. Differences in handling between policymakers both vertically and horizontally have created confusion, counterproductive, and even conflict between parties, resulting in the slow handling of the pandemic. In line with that, this paper looks at the forms of contestation between various policymakers, both central and regional. It analyzes the factors causing the power contestation in handling the pandemic. This study uses the results of observations, searches, and readings on sources of information from various online media and previous research. It turns out that our findings show that economic power has dominated and has become a force that guarantees policies and the logic of power in handling the pandemic. This paper suggests the need to expand the cases studied and add data sources to enable a more comprehensive understanding of the importance of handling the pandemic.